2014
DOI: 10.1155/2014/307025
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Intravenous Fosaprepitant and Ondansetron for the Prevention of Postoperative Nausea and Vomiting in Neurosurgery Patients: A Prospective, Randomized, Double-Blinded Study

Abstract: The incidence of postoperative nausea and vomiting (PONV) is 30–50% after surgery. PONV occurs frequently, especially after craniotomy. In this study, we investigated the preventive effects on PONV in a randomized study by comparing patients who had been administered fosaprepitant, a neurokinin-1 (NK1) receptor antagonist, or ondansetron intravenously. Sixty-four patients undergoing craniotomy were randomly allocated to receive fosaprepitant 150 mg i.v. (NK1 group, n = 32) or ondansetron 4 mg i.v. (ONS group, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(45 citation statements)
references
References 27 publications
0
45
0
Order By: Relevance
“…We determined the precise sample size for this trial based on our previous study that compared the preventive effects on PONV of fosaprepitant with that of ondansetron in neurosurgery patients [13]. The study demonstrated that the vomiting rate in the NK1 group was 6 % of 32 patients, while that in the ONS group was 50 % of 32 patients.…”
Section: Sample Size and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We determined the precise sample size for this trial based on our previous study that compared the preventive effects on PONV of fosaprepitant with that of ondansetron in neurosurgery patients [13]. The study demonstrated that the vomiting rate in the NK1 group was 6 % of 32 patients, while that in the ONS group was 50 % of 32 patients.…”
Section: Sample Size and Statistical Analysismentioning
confidence: 99%
“…Recently, we reported that fosaprepitant was more effective in decreasing the incidence of vomiting after neurosurgery [13] and gynecologic surgery [14]. On the basis of these Abstract Purpose Postoperative nausea and vomiting (PONV) is the most common complication after surgery, and opioid administration increases its incidence.…”
Section: Introductionmentioning
confidence: 99%
“…After examining titles and abstracts, 86 potentially relevant articles were identified, and a full-text review of each article was performed (see Appendix for a comprehensive list of these studies). A final number of 17 trials with a total of 1,433 participants were enrolled in this NMA (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24) (Figure 1). Fifteen trials assessed PON, whereas all 17 trails assessed POV.…”
Section: Evidence Synthesis Literature Searchmentioning
confidence: 99%
“…Female participants accounted for 52% of patients, with age ranging between 32 and 63 years. Three studies reported no intraoperative or postoperative dexamethasone use (21,22,24). The AED investigated included 5-hydroxytryptamine (5-HT3) receptor antagonists (granisetron, ondansetron, ramosetron, and tropisetron), neurokinin-1 (NK-1) receptor antagonists (fosaprepitant, aprepitant), butyrophenones (droperidol), corticosteroids (dexamethasone), phenothiazines (metoclopramide), and other unclassified drugs (gabapentin).…”
Section: Characteristics Of the Identified Trialsmentioning
confidence: 99%
“…PONV is considered by many patients to be more distressing than postoperative pain (2). The general incidence of PONV is approximately 50% and in a subset of high-risk patients, PONV rates can be as high as 70% (3,4,5,6). The four main risk factors of PONV include the female sex, a history of PONV or motion sickness, being a nonsmoker, and the use of postoperative opioids (7).…”
Section: Introductionmentioning
confidence: 99%